2021
DOI: 10.1111/ene.14857
|View full text |Cite
|
Sign up to set email alerts
|

Leukoencephalopathy with transient splenial lesions related to 5‐fluorouracil or capecitabine

Abstract: Background 5‐Fluorouracil (5‐FU) and its oral prodrug capecitabine have been rarely but consistently associated with acute central nervous system toxicity, including transient leukoencephalopathies involving the splenium of the corpus callosum. Methods We performed a retrospective search in the French Pharmacovigilance database (FPDB) (January 1985−July 2020) for adult patients affected by solid cancers who developed acute toxic leukoencephalopathies with splenial lesions following treatment with 5‐FU or capec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…These signs are suggestive of toxic leukoencephalopathy, as they reflect histological changes in the affected tissue, notably intramyelin and oligodendroglial edema (T2 and FLAIR hyperintensity), accumulation of vacuoles in myelin (DWI hyperintensity), and gadolinium enhancement could be explained by the blood-brain barrier (BBB) disruption due to the release of proinflammatory cytokines deleterious to the tight junctions of the BBB [ 2 , 10 , 11 ]. Perrain et al, in their series of 6 patients, reported no cases of gadolinium enhancement, which confirms the rarity of this sign and the atypical nature of our case [6] . DWI abnormalities are potentially reversible and can completely disappear [1] .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These signs are suggestive of toxic leukoencephalopathy, as they reflect histological changes in the affected tissue, notably intramyelin and oligodendroglial edema (T2 and FLAIR hyperintensity), accumulation of vacuoles in myelin (DWI hyperintensity), and gadolinium enhancement could be explained by the blood-brain barrier (BBB) disruption due to the release of proinflammatory cytokines deleterious to the tight junctions of the BBB [ 2 , 10 , 11 ]. Perrain et al, in their series of 6 patients, reported no cases of gadolinium enhancement, which confirms the rarity of this sign and the atypical nature of our case [6] . DWI abnormalities are potentially reversible and can completely disappear [1] .…”
Section: Discussionsupporting
confidence: 88%
“…Several clinical signs of 5-FU neurotoxicity have been described, such as headache, dysarthria, cerebellar syndrome, oculomotor disorders, confusion, cognitive disorders, Parkinson's syndrome, seizure, and coma [5] , [6] , [7] . Diagnosis of TL is based on a number of arguments, including the onset of symptoms after taking 5-FU, and the exclusion of other etiologies that may explain the neurological signs [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Upon capecitabine discontinuiation, all patients experienced full clinical-radiological recovery after a median of 8.5 days from symptom onset. 14 Obadia et al reported a 45-year-old woman treated by capecitabine for breast cancer with metastatic bone lesions, who presented with nausea, headaches, muscle cramps, dysarthria, and swallowing disorder. MRI showed bilateral and symmetric high signal intensities of deep white matter, corpus callosum, and corticospinal tracts with regression upon discontinuation.…”
Section: Overview Of the Reported Casesmentioning
confidence: 99%
“…Brain MRI showed T2/FLAIR hyperintensities in the corpus callosum, with diffusion restriction and no contrast enhancement. Upon capecitabine discontinuiation, all patients experienced full clinical‐radiological recovery after a median of 8.5 days from symptom onset 14 …”
Section: Overview Of the Reported Casesmentioning
confidence: 99%
See 1 more Smart Citation